Catalyzing Neurophysiology: Jacques Loeb, the Stazione Zoologica di Napoli, and a Growing Network of Brain Scientists, 1900s–1930s - Stahnisch, Frank W. (Frontiers in Neuroanatomy, 2019)
[Abstract was already submitted and reviewed for the Special Issue on the History of Neuroscience:] Even before the completion of his medical studies at the universities of Berlin, Munich, and Strasburg, as well as his M. D.-graduation – in 1884 – under Friedrich Goltz (1834- 1902), experimental biologist Jacques Loeb (1859-1924) became interested in degenerative and regenerative problems of brain anatomy. It can be supposed that he addressed these questions out of a growing dissatisfaction with leading perceptions about cerebral localization, as they had been advocated by the Berlin experimental neurophysiologists at the time. Instead, he followed Goltz and later Gustav Theodor Fechner (1801-1887) in elaborating a dynamic model of brain functioning vis-à-vis human perception and coordinated motion. To further pursue his scientific aims, Loeb moved to the Naples Zoological Station between 1889 and 1890, where he conducted a row of experimental series on regenerative phenomena in sea animals. He deeply admired the Italian marine research station for its overwhelming scientific liberalism along with the provision of considerable technical and intellectual support. In Naples, Loeb hoped to advance his research investigations on ‘tropisms’ further to form a reliable basis not only regarding the behaviour of lower animals, but also concerning perception and general neural capacities. He thought that he could demonstrate the existence of centre interdependence in the cerebral cortex of higher animals and humans, and was convinced that regenerative phenomena existed as plastic mechanisms influencing animal as well as human behavioural qualities. This new perspective on the organization of brain functioning and Loeb’s astonishing successes in experimental research with hydrozoa and echinoidea brought him in close contact with many neuroscientists of the early twentieth century. Yet, it is impossible to conceive of Loeb’s ground-breaking experiments without also taking his contemporary scientific network of teachers, colleagues, and local research milieus into account. All of these exerted a strong influence on a growing network of neuroscientific peers and research trainees who went on to interact in early brain research centres in Central Europe and North America. [..]